2023
DOI: 10.1186/s12909-023-04572-y
|View full text |Cite
|
Sign up to set email alerts
|

Burnout, grit and resilience among Jordanian orthopedic surgeons: a cross-sectional study

Mohammad Hamdan,
Bassem I. Haddad,
Mohammad Ali Alshrouf
et al.

Abstract: Background Burnout is a serious issue that affects physicians more than the general population; however, those with higher levels of grit and resilience have been shown to experience lower levels of burnout. The primary aim was to determine the prevalence of burnout among Jordanian orthopedic surgeons, explore its risk factors, and investigate the relationship between burnout and grit and resilience. Methods We conducted a questionnaire-based cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Age is also important when performing this regression analysis, as age has previously been reported to be an important confounder of psychological resilience and needs to be adjusted for when performing regression analysis. [19,20,21] Multiple imputation was chosen because it results in valid statistical inferences. [22] To assess the sensitivity of the results with respect to the multiple imputation method chosen, multiple imputation using the three methods available in the Multivariate Imputation by Chained Equation (MICE) package in R were performed (see Supplementary Table S2 online).…”
Section: Missing Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Age is also important when performing this regression analysis, as age has previously been reported to be an important confounder of psychological resilience and needs to be adjusted for when performing regression analysis. [19,20,21] Multiple imputation was chosen because it results in valid statistical inferences. [22] To assess the sensitivity of the results with respect to the multiple imputation method chosen, multiple imputation using the three methods available in the Multivariate Imputation by Chained Equation (MICE) package in R were performed (see Supplementary Table S2 online).…”
Section: Missing Datamentioning
confidence: 99%
“…Wang et al (2020) argued that senior healthcare workers have better experience and professional skills to address complex situations that arise in the workplace [19] Wang et al (2020). andHamdan et al (2023) reported that years in practice was positively associated with psychological resilience (p < 0.050 and p = 0.013, respectively) [19,21]. Afshari et al (2021) noted that an increase in healthcare workers' education and work experience may be linked to the progression of skills, which results in the development of positive coping strategies, leading to greater resilience.…”
mentioning
confidence: 99%
“…He said, “In the classic training program, we have taught how to perform surgery but not how to live as a surgeon.” Organizations can conduct regular surveys for feedback and support, flexible working hours when required, and medicolegal support in adverse outcomes or major complication cases. Regular and timely physical and mental health checkups and training programs focused on resilience, stress management, and coping strategies can enhance surgeons’ ability to navigate challenging situations [ 12 ]. At an individual level, one needs to chalk out a work–life balance.…”
mentioning
confidence: 99%